PENGARUH GOOD CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP PROFITABILITAS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Reynaldi Anwar; Deddy Rakhmad Hidayat (JEMBA : Jurnal Ekonomi Pembangunan, Manajemen dan bisnis, Akuntansi, 2021)
This study aims to provide an empirical explanation of the effect of good corporate governance and leverage on profitability in banking companies on the Indonesian stock exchange. The research method used in this research is descriptive-quantitative research approach. The unit of analysis of this research is banking companies registered as participants of the CGPI program from 2014-2018 with a purposive sampling technique. The collected data were analyzed using panel data regression analysis, the software used was Eviews 10. The results showed that good corporate governance has no effect on profitability, leverage has a positive effect on profitability and good corporate governance and leverage has a simultaneous effect on profitability